Optimization of Employee Performance at the Secretariat of the Regional People's Representative Council of Ciamis Regency - Mayunda, Sisi; Fariz, Bilqis Nabil; Lutfiyyah, Lulu; Sofarina, Qori; Garis, Regi Refian (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Employee performance is a very important aspect in terms of implementation and service in the government environment. Employee performance will greatly affect the good or bad processes in it. This study aims to determine and identify the factors that cause employee performance at the Ciamis Regency DPRD Secretariat that need to be continuously improved to be better, and to formulate steps to optimize employee performance at the DPRD Secretariat. This study uses a qualitative descriptive approach. Data collection methods in this study are interviews, documentation, analysis and observation. The results of the study indicate that when viewed from the measuring instrument in assessing employee performance, it turns out that there are several indicators that must be identified, these indicators include work performance, expertise/creativity, behavior and leadership. (Fachreza, Musnadi, & Majid, 2018). This aims to determine the factors that need to be optimized at the Ciamis Regency DPRD Secretariat, some of these factors such as the limited number of employees and not directly proportional to their workload, employee discipline is not evenly distributed so that some employee attendance is still decreasing. For this reason, it is necessary to make efforts to optimize employee performance in order to achieve the mission of the Ciamis DPRD Secretariat, namely to increase professionalism in supporting the realization of the role, duties and functions of the Ciamis Regency DPRD. Keywords : Employee Performance, DPRD Secretariat, Optimization, Productivity, Work Discipline